PATHOMORPHOLOGICAL ASPECTS OF RELEVANT GASTROINTESTINAL DISEASES IN NEWBORN AND GROWING CALVES - I. Kalkanov; Iv. Dinev (Trakia Journal of Sciences)
The emphasis of this literature overview is placed on the etiology, epidemiology, specific gross and microscopic pathological changes of the commonest gastrointestinal diseases in newborn and growing calves in dairy and beef farms. Neonatal diarrhea in calves is a multifactorial disease accompanied with high morbidity and mortality rates. It incurs considerable economic losses for cattle industry worldwide. The gastroenteritis in calves is most commonly of infectious or parasitic etiology and the most frequently involved enteropathogens are Cryptosporidium parvum, bovine rotaviruses (GRA BRV), bovine coronaviruses (BCoV), mucosal disease virus - bovine viral diarrhoea (BVDV) and Escherichia coli K99 (F5). Affected calves are from 24th hours to 30 days of age, and the appearance of the disease is largely dependent on the immunological status of newborn calves, the amount of ingested colostrum, whether dams are vaccinated or not during the dry period, and the conditions of housing of newborns. The specific gross and microscopic lesions of the gastrointestinal tract and of some parenchymal organs are essential for the diagnostics and differential diagnostics of reviewed diseases.